2018
DOI: 10.1111/apa.14282
|View full text |Cite
|
Sign up to set email alerts
|

Improving community health worker performance through supportive supervision: a randomised controlled implementation trial in Pakistan

Abstract: Aim: To assess the effect of enhanced supportive supervision of lady health workers (LHWs) by lady health supervisors on integrated community case management of childhood pneumonia and diarrhoea.Methods: A total of thirty-four supervisors were randomly assigned to intervention and comparison arms. The intervention included enhanced training of supervisors on supervisory skills and written feedback to LHWs by supervisors. The performance of both cadres was assessed three times. Household surveys judged caregive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 10 publications
(11 reference statements)
1
43
0
Order By: Relevance
“…Such a holistic conception requires viewing supervision not just as a dyadic relationship between a supervisee and their immediate line supervisor,10–14 but rather as a system operating at several levels with a range of functions involving different actors and relationships and forms of interaction, for example, one-on-one, group and peer supervision, and so on, simultaneously 7 9. In this sense, supervision can be thought of as a set of relationships embedded in the wider context of social and professional relationships and hierarchies within the health system.…”
Section: Introductionmentioning
confidence: 99%
“…Such a holistic conception requires viewing supervision not just as a dyadic relationship between a supervisee and their immediate line supervisor,10–14 but rather as a system operating at several levels with a range of functions involving different actors and relationships and forms of interaction, for example, one-on-one, group and peer supervision, and so on, simultaneously 7 9. In this sense, supervision can be thought of as a set of relationships embedded in the wider context of social and professional relationships and hierarchies within the health system.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the long timespan of this analysis (1989-2014), about a third of the study staff were involved in both the initial study and more recent follow-up and were able to collect comparable information during both periods. However, the supervision and support given to the study staff was more comprehensive in Study 1, which likely had a positive impact on health worker performance as suggested by other studies [35,41]. Similarly, in Study 1 community members could more easily meet with a member of the study team if their child became sick in between visits, but in Study 2 were more likely seek care elsewhere.…”
Section: Discussionmentioning
confidence: 82%
“…Repeated interactions with health workers and health and hygiene education may have contributed to this success. In Study 1, regular home visits from study staff and their visible presence in the community spanned 7 years, and there was intensive supervision of study staff, maintaining a high level of vigilance in the community and ensuring that the integrity of interventions was preserved [35]. Furthermore, 73% of children in Study 2 were living in a household that had participated in Study 1 and this may have helped preserve knowledge and experience in the community-base and ensured that interventions had a lasting impact.…”
Section: Discussionmentioning
confidence: 99%
“…A notable strength of this is study is that despite the long timespan of this analysis (1989-2014), about a third of the study staff were involved in both the initial study and more recent follow-up and were able to collect comparable information during both periods. However, the supervision and support given to the study staff was more comprehensive in Study 1, which likely had a positive impact on health worker performance as suggested by other studies [40,46]. Similarly, in Study 1 community members could more easily meet with a member of the study team if their child became sick in between visits, but in Study 2…”
Section: Discussionmentioning
confidence: 91%